DEFORMATION CHARACTERISTICS OF COMPUTATIONAL MODELS OF SOIL STRATA - Kendzera, A.; Semenova, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The method for determining of the deformation characteristics of the layers of computational models of soil strata for an equivalent linear and nonlinear modeling of soil response to seismic effects is considered in the article. The results of data collection, analysis and systematization of the results obtained in Japan and the USA laboratory and field studies of deformation characteristics of soils are presented. On this basis the database including the dependences of shear modules (G) and damping ratios (D) on the strain level (γ ) for different types of soils typical for sites located in the Ukraine was created. The results of the study of the factors influencing the G(γ) and D(γ) dependencies are analyzed. Based on the results of the analysis, the main parameters are identified that control the shape of the graphs of the indicated dependencies and allow to quickly determining with appropriate accuracy of the corresponding dependencies for each layer of the models of soil strata from the generated database. These are a plasticity index PL and a depth of occurrence of the clays and the particle size, their percentage and depth for sand. The paper presents the results of the investigation of the influence of epistemic errors that arise when selecting the dependences G(γ) and D(γ) for the ground layers of the design seismogeological model on the parameters of its amplitude-frequency characteristic, calculated by using the equivalent linear modeling of the soil response caused by earthquakes. The calculations were performed by using PROSHAKE software. It is found that the errors in determining of the deformation characteristics of ground layers in the calculation model lead to a shift in the maxima of the frequency response in the frequency domain, to a change in the amplification coefficients of the vibrations and to the appearance of "false" maxima at high frequencies. The database of G(γ) and D(γ) customized by the authors for different types of soils typical for sites located in Ukraine makes it possible to apply methods for modeling of the soil strata reaction caused by seismic impacts with taking into account the nonlinear behavior of soil response. The developed methodology for the formation of computed seismogeological models of the soil strata, by introducing the dependences G(γ) and D(γ), which reflect the nonlinear properties of soils, allows (at the level of modern knowledge) to approximate the calculated frequency characteristics of the soil to the real. As a result, the validity and accuracy of the determination of the quantitative parameters of the seismic hazard on the investigated construction and operational sites are increased, which is necessary for the development of effective measures for the seismic stability maintenance of the designed and existing facilities.
Keywords: soils; soil models; modeling of seismic oscillations; elastic and inelastic characteristics of the soil; epistemic and random errors; seismic impacts